The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Multi-Omics Characterization of a KIF1C Structural Variant in a Patient with a Complex Movement Disorder Partially Responsive to Deep Brain Stimulation - Mirja Thomsen; Max Borsche; Vicente A. Yépez; Dirk Rasche; Kristian K. Ullrich; Vera Tadic; Saad M. Abdelwakeel; Hauke Busch; Sören Franzenburg; Joanne Trinh; Christine Klein; Katja Lohmann; et al. (The Cerebellum, 2026)
Biallelic KIF1C variants are associated with a spectrum of neurological phenotypes, including spasticity, cerebellar ataxia, chorea, and dystonia. Most reported patients involve single-nucleotide variants, whereas copy number variants (CNVs) have been described only once in the PubMed-listed literature. The therapeutic potential of deep-brain stimulation (DBS) in KIF1C -related disease has not yet been evaluated. We report a patient presenting with spasticity, ataxia, dystonia, and head tremor, in whom prior exome sequencing was inconclusive. A multi-omics approach was applied, including optical genome mapping (OGM), genome sequencing, and transcriptome sequencing. The clinical effect of DBS was assessed. OGM revealed a homozygous KIF1C Exon 17–18 deletion, retrospectively detectable in exome and genome data but initially missed by sequence analysis. Transcriptome sequencing demonstrated significantly reduced KIF1C expression and absence of normally spliced transcripts around those exons, consistent with a loss-of-function mechanism. DBS led to partial clinical improvement, with notable reduction of dystonia and head tremor. Structural variants may be an underrecognized cause of complex movement disorders involving spasticity, ataxia, and dystonia. Diagnostic methods specifically targeting structural variation, such as OGM or CNV analysis of short-read data, can be essential for diagnosis. Transcriptome data add valuable functional insight. This report also suggests that DBS may offer symptomatic benefit in KIF1C -associated disease, particularly for dystonic signs.

The electric vehicle transition: effects on copper supply dynamics in a net-zero future - S. Duex; P. Busch; A. Kendall (Resources, Conservation and Recycling, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

How mixed messages may be better than avoidance in climate change education - Kathryn Stevenson; K. C. Busch; M. Nils Peterson; Danielle A. Frank; Regina Ayala Chavez (Journal of Environmental Studies and Sciences, 2025)

Climate (in)action? The relationship between CEO early-life experiences and corporate climate policies - Wiebke Szymczak; Simone A. Wagner; Timo Busch (Ecological Economics, 2025)

P21-02 Comparing the effects of active substances and plant protection products in vitro using gene expression patterns in HepaRG cells and zebrafish embryos - A. Stagkos-Georgiadis; I. Suciu; W. Busch; D. Bloch (Toxicology Letters, 2025)

Population genetic structure in two contrasting human-altered environments of yellow pygmy rice rat Oligoryzomys flavescens - E. Muschetto; I. E. Gómez Villafañe; M. Scaltritti; J. Fraschina; V. León; L. Adduci; D. Hancke; S. Guidobono; G. R. Cueto; M. A. Tripodi; E. Hasson; M. Busch; et al. (Oecologia, 2025)

Adult withdrawal of long-term Benzophenone-3 treatment induces regression of mammary ductal branching in a diet-dependent manner - Calista Busch; Anastasia Kariagina; Elena Morozova; Mitchell A. Borin; Richard C. Schwartz (Food and Chemical Toxicology, 2025)

Petrophysical Characterization of Metamorphic Rocks using X-ray Micro-CT data – Implications for fluid flow - Ritwik Chakraborty; Michael Späth; Akash Kumar; Benjamin Busch; Britta Nestler; Manish A. Mamtani; Christoph Hilgers (Journal of Structural Geology, 2025)

Field evaluation of cat fur and TMT odours as repellents of commensal rodents in poultry farms - Gabriela S. Hillar; Vanina A. León; María Busch; Dana Esquenazi; Jimena Fraschina (Applied Animal Behaviour Science, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Research and educational applications of the Aerojet General Nucleonics 201-M at the University of New Mexico - Rowdy Davis; Christopher M. Perfetti; Robert D. Busch; Larry L. Wetzel; Carl A. Willis (Annals of Nuclear Energy, 2024)

A novel in vitro high-content imaging assay for the prediction of drug-induced lung toxicity - Paul A. Fitzpatrick; Julia Johansson; Gareth Maglennon; Ian Wallace; Ramon Hendrickx; Marianna Stamou; Kinga Balogh Sivars; Susann Busch; Linnea Johansson; Natalie Van Zuydam; Kelley Patten; Per M. Åberg; et al. (Archives of Toxicology, 2024)
The development of inhaled drugs for respiratory diseases is frequently impacted by lung pathology in non-clinical safety studies. To enable design of novel candidate drugs with the right safety profile, predictive in vitro lung toxicity assays are required that can be applied during drug discovery for early hazard identification and mitigation. Here, we describe a novel high-content imaging-based screening assay that allows for quantification of the tight junction protein occludin in A549 cells, as a model for lung epithelial barrier integrity. We assessed a set of compounds with a known lung safety profile, defined by clinical safety or non-clinical in vivo toxicology data, and were able to correctly identify 9 of 10 compounds with a respiratory safety risk and 9 of 9 compounds without a respiratory safety risk (90% sensitivity, 100% specificity). The assay was sensitive at relevant compound concentrations to influence medicinal chemistry optimization programs and, with an accessible cell model in a 96-well plate format, short protocol and application of automated imaging analysis algorithms, this assay can be readily integrated in routine discovery safety screening to identify and mitigate respiratory toxicity early during drug discovery. Interestingly, when we applied physiologically-based pharmacokinetic (PBPK) modelling to predict epithelial lining fluid exposures of the respiratory tract after inhalation, we found a robust correlation between in vitro occludin assay data and lung pathology in vivo, suggesting the assay can inform translational risk assessment for inhaled small molecules.

Entanglement and ingestion of microfibers by the oyster pea crab Zaops ostreum, an endosymbiont of the eastern oyster Crassostrea virginica - Linda J. Walters; Sidney J. Busch; Sophia Vermeulen; Casey A. Craig (Marine Pollution Bulletin, 2024)

Role of pH-sensing receptors in colitis - Martin Hausmann; Klaus Seuwen; Cheryl de Vallière; Moana Busch; Pedro A. Ruiz; Gerhard Rogler (Pflügers Archiv - European Journal of Physiology, 2024)
Low pH in the gut is associated with severe inflammation, fibrosis, and colorectal cancer (CRC) and is a hallmark of active inflammatory bowel disease (IBD). Subsequently, pH-sensing mechanisms are of interest for the understanding of IBD pathophysiology. Tissue hypoxia and acidosis—two contributing factors to disease pathophysiology—are linked to IBD, and understanding their interplay is highly relevant for the development of new therapeutic options. One member of the proton-sensing G protein-coupled receptor (GPCR) family, GPR65 (T-cell death-associated gene 8, TDAG8), was identified as a susceptibility gene for IBD in a large genome-wide association study. In response to acidic extracellular pH, GPR65 induces an anti-inflammatory response, whereas the two other proton-sensing receptors, GPR4 and GPR68 (ovarian cancer G protein-coupled receptor 1, OGR1), mediate pro-inflammatory responses. Here, we review the current knowledge on the role of these proton-sensing receptors in IBD and IBD-associated fibrosis and cancer, as well as colitis-associated cancer (CAC). We also describe emerging small molecule modulators of these receptors as therapeutic opportunities for the treatment of IBD.

Global patterns of allochthony in stream–riparian meta‐ecosystems - Daniel C. Allen; James Larson; Christina A. Murphy; Erica A. Garcia; Kurt E. Anderson; Michelle H. Busch; Alba Argerich; Alice M. Belskis; Kierstyn T. Higgins; Brooke E. Penaluna; Veronica Saenz; Jay Jones; et al. (Ecology Letters, 2024)
Ecosystems that are coupled by reciprocal flows of energy and nutrient subsidies can be viewed as a single “meta‐ecosystem.” Despite these connections, the reciprocal flow of subsidies is greatly asymmetrical and seasonally pulsed. Here, we synthesize existing literature on stream–riparian meta‐ecosystems to quantify global patterns of the amount of subsidy consumption by organisms, known as “allochthony.” These resource flows are important since they can comprise a large portion of consumer diets, but can be disrupted by human modification of streams and riparian zones. Despite asymmetrical subsidy flows, we found stream and riparian consumer allochthony to be equivalent. Although both fish and stream invertebrates rely on seasonally pulsed allochthonous resources, we find allochthony varies seasonally only for fish, being nearly three times greater during the summer and fall than during the winter and spring. We also find that consumer allochthony varies with feeding traits for aquatic invertebrates, fish, and terrestrial arthropods, but not for terrestrial vertebrates. Finally, we find that allochthony varies by climate for aquatic invertebrates, being nearly twice as great in arid climates than in tropical climates, but not for fish. These findings are critical to understanding the consequences of global change, as ecosystem connections are being increasingly disrupted.

A novel climate and health decision support platform: Approach, outputs, and policy considerations - Jeremy J. Hess; Timothy J. Sheehan; Alyssa Miller; Rad Cunningham; Nicole A. Errett; Tania Busch Isaksen; Jason Vogel; Kristie L. Ebi (Environmental Research, 2023)

Low rate of detection of SARS-CoV-2 RNA in deceased tissue donors - Melissa A. Greenwald; Eduard Grebe; Valerie Green; Alyce Linthurst Jones; Jeffrey M. Linnen; Phillip Williamson; Michael P. Busch; Matthew J. Kuehnert (Cell and Tissue Banking, 2023)
Given the possibility for disease transmission, this study was performed to determine whether there is detectable SARS-CoV-2 viral RNA in the blood of deceased tissue donors. A retrospective analysis of blood samples from eligible deceased tissue donors from Oct 2019 through June 2020 was performed. Plasma aliquots were initially tested with a SARS-CoV-2 NAT Assay; positive samples were further tested using an alternate NAT and an antibody assay. The proportion of donors with confirmed RNAemia and 95% confidence intervals were computed. Of donor samples collected in 2019, 894 yielded valid results, with 6 initially positive, none of which confirmed positive by alternate NAT. Of donor samples collected in 2020, 2562 yielded valid initial NAT results, with 21 (0.8%) initially positive. Among those, 3 were confirmed by alternate NAT, 17 were not confirmed, and 1 had an invalid alternate NAT result. The rate of SARS-CoV-2 RNAemia in deceased tissue donors is approximately 1 per 1000, and it is unknown whether this RNAemia reflects the presence of infectious virus. Given these results, the risk of transmission through tissue is thought likely to be low.

Indicators of water use efficiency across diverse agroecosystems and spatiotemporal scales - David L. Hoover; Lori J. Abendroth; Dawn M. Browning; Amartya Saha; Keirith Snyder; Pradeep Wagle; Lindsey Witthaus; Claire Baffaut; Joel A. Biederman; David D. Bosch; Rosvel Bracho; Dennis Busch; et al. (Science of The Total Environment, 2023)

GMO analysis results from official food control laboratories in Germany from 2017 to 2021 - Hans-Ulrich Waiblinger; Christine A. Eichner; Gabriele Näumann; Ulrich Busch (Journal of Consumer Protection and Food Safety, 2023)
In Germany, genetically modified organisms (GMO) analysis of food samples collected within the official food control is performed by the laboratories of the Federal States. The present report shows GMO analysis results from food samples of the years 2017 to 2021, including contaminations by unauthorized GMO, as well as genetically modified (GM) plant events authorized in the European Union. In addition to previous publications, evaluation of the aggregated food samples analysed for GMO components is shown. During this timeframe, 1077 (7.1%) out of 15,145 samples contained genetic modification. In 43 samples, DNA sequences of unauthorized GM plants were found. Additionally, for food derived from soybean, evaluations according to different product categories and the agronomic production (conventional and organic farming) are shown. Whereas in products from organic farming and in conventional soybeans labelled “without genetic engineering” GM soybeans were detected in 6.1% and 8.9%, of all tested samples, respectively, nearly 30% of all conventional soy samples yielded positive results below 0.1%. However, only in 0.7% of the overall analysed 5424 soybean samples GMO percentages of more than 0.1% were obtained. Generally, authorized GM plants were only found at low contamination levels. The labelling threshold of 0.9% for GM ingredients was exceeded only in 0.2% (maize) and 0.1% (soybean) samples, respectively. For monitoring purposes and risk evaluation, the data collection shall be continued.

Evaluating environmental controls on the exoskeleton density of larval Dungeness crab via micro computed tomography - Casey P. Saenger; Paul McElhany; Emily L. Norton; D. Shallin Busch; Samantha A. Siedlecki; Simone R. Alin; Richard A. Feely; Albert J. Hermann; Nina Bednaršek (Frontiers in Marine Science, 2023)
Dungeness crab ( Metacarcinus magister ) have significant socioeconomic value, but are threatened by ocean acidification (OA) and other environmental stressors that are driven by climate change. Despite evidence that adult harvests are sensitive to the abundance of larval populations, relatively little is known about how Dungeness megalopae will respond to these stressors. Here we evaluate the ability to use micro-computed tomography (μCT) to detect variations in megalope exoskeleton density and how these measurements reflect environmental variables and calcification mechanisms. We use a combination of field data, culture experiments, and model simulations to suggest resolvable differences in density are best explained by minimum pH at the time zoeae molt into megalopae. We suggest that this occurs because more energy must be expended on active ion pumping to reach a given degree of calcite supersaturation at lower pH. Energy availability may also be reduced due to its diversion to other coping mechanisms. Alternate models based on minimum temperature at the time of the zoea-megalope molt are nearly as strong and complicate the ability to conclusively disentangle pH and temperature influences. Despite this, our results suggest that carryover effects between life stages and short-lived extreme events may be particularly important controls on exoskeleton integrity. μCT-based estimates of exoskeleton density are a promising tool for evaluating the health of Dungeness crab populations that will likely provide more nuanced information than presence-absence observations, but future in situ field sampling and culture experiments are needed to refine and validate our results.

Interlaboratory comparison of an intestinal triple culture to confirm transferability and reproducibility - Angela A. M. Kämpfer; Ume-Kulsoom Shah; Shui L. Chu; Mathias Busch; Veronika Büttner; Ruiwen He; Barbara Rothen-Rutishauser; Roel P. F. Schins; Gareth J. Jenkins (In vitro models, 2022)
The development and improvement of advanced intestinal in vitro models has received increasing attention in recent years. While the availability of relevant in vitro models is pivotal to advance the replacement and reduction of animal use in research, their robustness is a crucial determinant for intra- and interlaboratory reproducibility. We have developed a standard protocol to build a triple culture model combining two types of human intestinal epithelial cells (Caco-2, HT29-MTX-E12) and macrophages (THP-1), which was tested for transferability and reproducibility between three laboratories. The epithelial tissue barrier development and triple culture stability were investigated as well as the models’ responses to the non-steroidal anti-inflammatory drug diclofenac in terms of barrier integrity, cytotoxicity, and cytokine release. The results of two partner laboratories were compared to previously established benchmark results and quality criteria. For the epithelial co-cultures, the results were overall highly comparable between the laboratories. The addition of THP-1 cells resulted in increased variability and reduced reproducibility. While good correlation was achieved in several endpoints, others showed substantial response differences between the laboratories. Some variations may be addressed with training or demonstrations, whereas others might be related to fundamental differences in the cell lines introduced during routine cell culture and maintenance. Our results underline the importance of interlaboratory transfer studies using standardised experimental procedures, including defined quality criteria and benchmarks, as well as of training when newly establishing complex in vitro models in laboratories.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Evaluation of Cardiotonic Steroid Modulation of Cellular Cholesterol and Phospholipid - Lilian N. D. Silva; Israel J. P. Garcia; Jessica M. M. Valadares; Marco Tulio C. Pessoa; Marina Marques Toledo; Matheus V. Machado; Mileane Souza Busch; Isabella Rocha; José Augusto F. P. Villar; Georgia C. Atella; Herica L. Santos; Vanessa F. Cortes; et al. (The Journal of Membrane Biology, 2021)

Reducing Data Deficiencies: Preliminary Elasmobranch Fisheries Surveys in India, Identify Range Extensions and Large Proportions of Female and Juvenile Landings - Shaili Johri; Isabella Livingston; Anjani Tiwari; Jitesh Solanki; Anissa Busch; Isabel Moreno; Sam R. Fellows; Michael P. Doane; Elizabeth A. Dinsdale (Frontiers in Marine Science, 2021)
Chondrichthyes, an ancient and diverse class of vertebrates, are crucial to the health of marine ecosystems. Excessive demand for chondrichthyan products has increased fishing pressure, threatening ∼30% of species with extinction in recent decades. India is the second-largest shark landing nation globally and the province of Gujarat, is the largest contributor to its shark exports. Despite their significant contribution to global fish supplies, chondrichthyan fisheries in Gujarat remain understudied and many species, data deficient, posing challenges to the conservation of remaining populations in the region. Here, we report results from taxonomic assessment of elasmobranchs at four key landing sites in Gujarat. We identified thirty-one species of sharks and rays with a significant bias toward capture of females and juveniles by fisheries. Our data indicate the presence of nursery areas for species such as Sphyrna lewini and Rhynchobatus laevis in the neritic areas off Gujarat. Further, we discovered extensions of the current distribution range for three species - Torpedo sinuspersici , Carcharhinus sorrah , and Rhinobatos punctifer . Taxonomic identities for a subset of species were confirmed using genomic analyses conducted with portable DNA sequencing tools. We present assessments for six data deficient species in the region – Rhinobatos annandalei , Rhinoptera jayakari , Maculabatis bineeshi, Pateobatis bleekeri, T. sinuspersici , and Carcharhinus amboinensis. Our investigation underscores species with urgent conservation needs and reduces data deficiencies. These data will inform and pivot future scientific and conservation efforts to protect remaining populations of some of the most vulnerable Chondrichthyes in the Arabian Seas Region.

Marine Citizen Science: Current State in Europe and New Technological Developments - Carlos Garcia-Soto; Jan J. C. Seys; Oliver Zielinski; J. A. Busch; S. I. Luna; Jose Carlos Baez; C. Domegan; K. Dubsky; I. Kotynska-Zielinska; P. Loubat; Francesca Malfatti; G. Mannaerts; et al. (Frontiers in Marine Science, 2021)
Marine citizen science is emerging with promising opportunities for science, policy and public but there is still no comprehensive overview of the current state in Europe. Based on 127 projects identified for the North Sea area we estimate there might be as much as 500 marine and coastal citizen science projects running in Europe, i.e., one marine citizen science project per ∼85 km of coastline, with an exponential growth since 1990. Beach-based projects are more accessible and hence most popular (60% of the projects), and the mean duration of the projects is 18–20 years. Current trends, topics, organizers, aims, and types of programme in terms of participation are presented in this overview. Progress in marine citizen science is specially enabled and promoted through technological developments. Recent technological advances and best practise examples are provided here, untapping the potential of smart mobile apps, do-it-yourself (DIY) technologies, drones, and artificial intelligence (AI) web services.

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Critical review: incorporating the arrangement of mitochondria and chloroplasts into models of photosynthesis and carbon isotope discrimination - Nerea Ubierna; Lucas A. Cernusak; Meisha Holloway-Phillips; Florian A. Busch; Asaph B. Cousins; Graham D. Farquhar (Photosynthesis Research, 2019)

Climate‐driven reduction of genetic variation in plant phenology alters soil communities and nutrient pools - Ian M. Ware; Michael E. Van Nuland; Jennifer A. Schweitzer; Zamin Yang; Christopher W. Schadt; Lindsay C. Sidak‐Loftis; Nathan E. Stone; Joseph D. Busch; David M. Wagner; Joseph K. Bailey (Global Change Biology, 2019)
We examined the hypothesis that climate‐driven evolution of plant traits will influence associated soil microbiomes and ecosystem function across the landscape. Using a foundation tree species, Populus angustifolia , observational and common garden approaches, and a base population genetic collection that spans 17 river systems in the western United States, from AZ to MT, we show that (a) as mean annual temperature (MAT) increases, genetic and phenotypic variation for bud break phenology decline; (b) soil microbiomes, soil nitrogen (N), and soil carbon (C) vary in response to MAT and conditioning by trees; and (c) with losses of genetic variation due to warming, population‐level regulation of community and ecosystem functions strengthen. These results demonstrate a relationship between the potential evolutionary response of populations and subsequent shifts in ecosystem function along a large temperature gradient.

Risks of ocean acidification in the California Current food web and fisheries: ecosystem model projections - Kristin N. Marshall; Isaac C. Kaplan; Emma E. Hodgson; Albert Hermann; D. Shallin Busch; Paul McElhany; Timothy E. Essington; Chris J. Harvey; Elizabeth A. Fulton (Global Change Biology, 2017)
The benefits and ecosystem services that humans derive from the oceans are threatened by numerous global change stressors, one of which is ocean acidification. Here, we describe the effects of ocean acidification on an upwelling system that already experiences inherently low pH conditions, the California Current. We used an end‐to‐end ecosystem model (Atlantis), forced by downscaled global climate models and informed by a meta‐analysis of the pH sensitivities of local taxa, to investigate the direct and indirect effects of future pH on biomass and fisheries revenues. Our model projects a 0.2‐unit drop in pH during the summer upwelling season from 2013 to 2063, which results in wide‐ranging magnitudes of effects across guilds and functional groups. The most dramatic direct effects of future pH may be expected on epibenthic invertebrates (crabs, shrimps, benthic grazers, benthic detritivores, bivalves), and strong indirect effects expected on some demersal fish, sharks, and epibenthic invertebrates (Dungeness crab) because they consume species known to be sensitive to changing pH . The model's pelagic community, including marine mammals and seabirds, was much less influenced by future pH . Some functional groups were less affected to changing pH in the model than might be expected from experimental studies in the empirical literature due to high population productivity (e.g., copepods, pteropods). Model results suggest strong effects of reduced pH on nearshore state‐managed invertebrate fisheries, but modest effects on the groundfish fishery because individual groundfish species exhibited diverse responses to changing pH . Our results provide a set of projections that generally support and build upon previous findings and set the stage for hypotheses to guide future modeling and experimental analysis on the effects of OA on marine ecosystems and fisheries.

The association of children’s mathematic abilities with both adults’ cognitive abilities and intrinsic fronto-parietal networks is altered in preterm-born individuals - J. G. Bäuml; C. Meng; M. Daamen; N. Baumann; B. Busch; P. Bartmann; D. Wolke; H. Boecker; A. Wohlschläger; C. Sorg; Julia Jaekel (Brain Structure and Function, 2017)

Extensive and interrelated subcortical white and gray matter alterations in preterm-born adults - C. Meng; J. G. Bäuml; M. Daamen; J. Jaekel; J. Neitzel; L. Scheef; B. Busch; N. Baumann; H. Boecker; C. Zimmer; P. Bartmann; D. Wolke; et al. (Brain Structure and Function, 2016)

Increased mortality associated with extreme-heat exposure in King County, Washington, 1980–2010 - Tania Busch Isaksen; Richard A. Fenske; Elizabeth K. Hom; You Ren; Hilary Lyons; Michael G. Yost (International Journal of Biometeorology, 2016)

Evaluating markers of epithelial-mesenchymal transition to identify cancer patients at risk for metastatic disease - Evan L. Busch; Temitope O. Keku; David B. Richardson; Stephanie M. Cohen; David A. Eberhard; Christy L. Avery; Robert S. Sandler (Clinical & Experimental Metastasis, 2016)

Atlantic salmon, S almo salar L . are broadly susceptible to isolates representing the N orth A merican genogroups of infectious hematopoietic necrosis virus - G Kurath; J R Winton; O B Dale; M K Purcell; K Falk; R A Busch (Journal of Fish Diseases, 2016)
Beginning in 1992, three epidemic waves of infectious hematopoietic necrosis, often with high mortality, occurred in farmed A tlantic salmon S almo salar L . on the west coast of N orth A merica. We compared the virulence of eleven strains of infectious hematopoietic necrosis virus ( IHNV ), representing the U , M and L genogroups, in experimental challenges of juvenile A tlantic salmon in freshwater. All strains caused mortality and there was wide variation within genogroups: cumulative mortality for five U ‐group strains ranged from 20 to 100%, four M ‐group strains ranged 30‐63% and two L ‐group strains varied from 41 to 81%. Thus, unlike P acific salmonids, there was no apparent correlation of virulence in a particular host species with virus genogroup. The mortality patterns indicated two different phenotypes in terms of kinetics of disease progression and final per cent mortality, with nine strains having moderate virulence and two strains (from the U and L genogroups) having high virulence. These phenotypes were investigated by histopathology and immunohistochemistry to describe the variation in the course of IHNV disease in A tlantic salmon. The results from this study demonstrate that IHNV may become a major threat to farmed A tlantic salmon in other regions of the world where the virus has been, or may be, introduced.

Flicker-Induced Time Dilation Does Not Modulate EEG Correlates of Temporal Encoding - Sophie K. Herbst; Maximilien Chaumon; Trevor B. Penney; Niko A. Busch (Brain Topography, 2015)

Implications of p75NTR for dentate gyrus morphology and hippocampus-related behavior revisited - M. Dokter; R. Busch; R. Poser; M. A. Vogt; V. von Bohlen und Halbach; P. Gass; K. Unsicker; O. von Bohlen und Halbach (Brain Structure and Function, 2015)

Method Transfer, Partial Validation, and Cross Validation: Recommendations for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - R. J. Briggs; R. Nicholson; F. Vazvaei; J. Busch; M. Mabuchi; K. S. Mahesh; M. Brudny-Kloeppel; N. Weng; P. A. R. Galvinas; P. Duchene; Pei Hu; R. W. Abbott (The AAPS Journal, 2014)

Opinion: The red-light response of stomatal movement is sensed by the redox state of the photosynthetic electron transport chain - Florian A. Busch (Photosynthesis Research, 2014)

Correction of hyperspectral reflectance measurements for surface objects and direct sun reflection on surface waters - Julia A. Busch; John D. Hedley; Oliver Zielinski (International Journal of Remote Sensing, 2013)

Ecological commonalities among pelagic fishes: comparison of freshwater ciscoes and marine herring and sprat - Thomas Mehner; Susan Busch; Catriona Clemmesen; Ingeborg Palm Helland; Franz Hölker; Jan Ohlberger; Myron A. Peck (Marine Biology, 2012)

Oxygen minimum zones harbour novel viral communities with low diversity - Noriko Cassman; Alejandra Prieto‐Davó; Kevin Walsh; Genivaldo G. Z. Silva; Florent Angly; Sajia Akhter; Katie Barott; Julia Busch; Tracey McDole; J. Matthew Haggerty; Dana Willner; Gadiel Alarcón; et al. (Environmental Microbiology, 2012)
Summary Oxygen minimum zones ( OMZs ) are oceanographic features that affect ocean productivity and biodiversity, and contribute to ocean nitrogen loss and greenhouse gas emissions. Here we describe the viral communities associated with the E astern T ropical S outh P acific ( ETSP ) OMZ off I quique, C hile for the first time through abundance estimates and viral metagenomic analysis. The viral‐to‐microbial ratio ( VMR ) in the ETSP OMZ fluctuated in the oxycline and declined in the anoxic core to below one on several occasions. The number of viral genotypes (unique genomes as defined by sequence assembly) ranged from 2040 at the surface to 98 in the oxycline, which is the lowest viral diversity recorded to date in the ocean. Within the ETSP OMZ viromes, only 4.95% of genotypes were shared between surface and anoxic core viromes using reciprocal BLASTn sequence comparison. ETSP virome comparison with surface marine viromes ( S argasso S ea, G ulf of M exico, K ingman R eef, C hesapeake B ay) revealed a dissimilarity of ETSP OMZ viruses to those from other oceanic regions. From the 1.4 million non‐redundant DNA sequences sampled within the altered oxygen conditions of the ETSP OMZ , more than 97.8% were novel. Of the average 3.2% of sequences that showed similarity to the SEED non‐redundant database, phage sequences dominated the surface viromes, eukaryotic virus sequences dominated the oxycline viromes, and phage sequences dominated the anoxic core viromes. The viral community of the ETSP OMZ was characterized by fluctuations in abundance, taxa and diversity across the oxygen gradient. The ecological significance of these changes was difficult to predict; however, it appears that the reduction in oxygen coincides with an increased shedding of eukaryotic viruses in the oxycline, and a shift to unique viral genotypes in the anoxic core.

A Pool of Pairs of Related Objects (POPORO) for Investigating Visual Semantic Integration: Behavioral and Electrophysiological Validation - Lyudmyla Y. Kovalenko; Maximilien Chaumon; Niko A. Busch (Brain Topography, 2012)

Comparative analysis of Neph gene expression in mouse and chicken development - Linus A. Völker; Marianne Petry; Mohammad Abdelsabour-Khalaf; Heiko Schweizer; Faisal Yusuf; Tilman Busch; Bernhard Schermer; Thomas Benzing; Beate Brand-Saberi; Oliver Kretz; Martin Höhne; Andreas Kispert (Histochemistry and Cell Biology, 2012)

Are the closed landfills recovered habitats for small rodents? A case study in a riparian site, Buenos Aires, Argentina - María Florencia Carballido; Pablo Arístide; María Busch; Emilio A. Cittadino; Isabel E. Gómez Villafañe (Urban Ecosystems, 2011)

Narrow species concepts in the Frullania dilatata–appalachiana–eboracensis complex (Porellales, Jungermanniopsida): evidence from nuclear and chloroplast DNA markers - A. Bombosch; A. Wieneke; A. Busch; R. Jonas; J. Hentschel; H.-P. Kreier; B. Shaw; A. J. Shaw; J. Heinrichs (Plant Systematics and Evolution, 2010)

Detecting marine hazardous substances and organisms: sensors for pollutants, toxins, and pathogens - O. Zielinski; J. A. Busch; A. D. Cembella; K. L. Daly; J. Engelbrektsson; A. K. Hannides; H. Schmidt (Ocean Science, 2009)
Marine environments are influenced by a wide diversity of anthropogenic and natural substances and organisms that may have adverse effects on human health and ecosystems. Real-time measurements of pollutants, toxins, and pathogens across a range of spatial scales are required to adequately monitor these hazards, manage the consequences, and to understand the processes governing their magnitude and distribution. Significant technological advancements have been made in recent years for the detection and analysis of such marine hazards. In particular, sensors deployed on a variety of mobile and fixed-point observing platforms provide a valuable means to assess hazards. In this review, we present state-of-the-art of sensor technology for the detection of harmful substances and organisms in the ocean. Sensors are classified by their adaptability to various platforms, addressing large, intermediate, or small areal scales. Current gaps and future demands are identified with an indication of the urgent need for new sensors to detect marine hazards at all scales in autonomous real-time mode. Progress in sensor technology is expected to depend on the development of small-scale sensor technologies with a high sensitivity and specificity towards target analytes or organisms. However, deployable systems must comply with platform requirements as these interconnect the three areal scales. Future developments will include the integration of existing methods into complex and operational sensing systems for a comprehensive strategy for long-term monitoring. The combination of sensor techniques on all scales will remain crucial for the demand of large spatial and temporal coverage.

Laboratory Experiments on Environmental Friendly Means to Improve Coalbed Methane Production by Carbon Dioxide/Flue Gas Injection - S. Mazumder; K. H. A. A. Wolf; P. van Hemert; A. Busch (Transport in Porous Media, 2008)

Dynamics of well-folded and natively disordered proteins in solution: a time-of-flight neutron scattering study - A. M. Gaspar; M.-S. Appavou; S. Busch; T. Unruh; W. Doster (European Biophysics Journal, 2008)

Anticipation of natural stimuli modulates EEG dynamics: physiology and simulation - Ingo Fründ; Jeanette Schadow; Niko A. Busch; Nicole Naue; Ursula Körner; Christoph S. Herrmann (Cognitive Neurodynamics, 2008)

Endocrine responsiveness to social challenges in northern and southern hemisphere populations of Zonotrichia - John C. Wingfield; Simone L. Meddle; Ignacio Moore; Shallin Busch; Douglas Wacker; Sharon Lynn; Aaron Clark; Rodrigo A. Vasquez; Elizabeth Addis (Journal of Ornithology, 2007)

“Technically Unavoidable” in Terms of Genetically Modified Organisms – an Approach for Food Control - H.-U. Waiblinger; N. Graf; D. Mäde; K. Woll; U. Busch; B. Holland; H. Pilsl; G. Naeumann; R. Reiting; B. Ehrentreich; M. Schulze; B. Tschirdewahn; et al. (Journal of Consumer Protection and Food Safety, 2007)

Nachweis Shigatoxin-bildender / Enterohämorrhagischer Escherichia coli (STEC / EHEC) mittels Real-Time PCR - U. Busch; I. Huber; U. Messelhäusser; S. Hörmansdorfer; A. Sing (Journal of Consumer Protection and Food Safety, 2007)

The Use of Poly(Sodium N-Undecanoyl-l-Leucylvalinate), Poly(Sodium N-Undecanoyl-l-Leucinate) and Poly(Sodium N-Undecanoyl-l-Valinate) Surfactants as Chiral Selectors for Determination of Enantiomeric Composition of Samples by Multivariate Regression Modeling of Fluorescence Spectral Data - Sayo O. Fakayode; Alicia A. Williams; Marianna A. Busch; Kenneth W. Busch; Isiah M. Warner (Journal of Fluorescence, 2006)

Genetic structure in a solitary rodent ( Ctenomys talarum ): implications for kinship and dispersal - A. P. CUTRERA; E. A. LACEY; C. BUSCH (Molecular Ecology, 2005)
The genetic structure of a population provides critical insights into patterns of kinship and dispersal. Although genetic evidence of kin structure has been obtained for multiple species of social vertebrates, this aspect of population biology has received considerably less attention among solitary taxa in which spatial and social relationships are unlikely to be influenced by kin selection. Nevertheless, significant kin structure may occur in solitary species, particularly if ecological or life history traits limit individual vagility. To explore relationships between genetic structure, kinship, and dispersal in a solitary vertebrate, we compared patterns of genetic variation in two demographically distinct populations of the talar tuco‐tuco ( Ctenomys talarum ), a solitary species of subterranean rodent from Buenos Aires Province, Argentina. Based on previous field studies of C. talarum at Mar de Cobo (MC) and Necochea (NC), we predicted that natal dispersal in these populations is male biased, with dispersal distances for males and females being greater at NC. Analyses of 12 microsatellite loci revealed that in both populations, kin structure was more apparent among females than among males. Between populations, kinship and genetic substructure were more pronounced at MC. Thus, our findings were consistent with predicted patterns of dispersal for these animals. Collectively, these results indicate that populations of this solitary species are characterized by significant kin structure, suggesting that, even in the absence of sociality and kin selection, the spatial distributions and movements of individuals may significantly impact patterns of genetic diversity among conspecifics.

Epidemiology of rubella infections in Austria: important lessons to be learned - B. Falkensammer; G. Walder; D. Busch; A. Gieauf; M. Dierich; R. Wrzner (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Inhibitors of ATP-sensitive potassium channels in guinea pig isolated ischemic hearts - A. Weyermann; H. Vollert; A. E. Busch; M. Bleich; H. Ggelein (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Granulocyte colony-stimulating factor (G-CSF) reduces not only gram-negative but also gram-positive infection-associated proinflammatory cytokine release by interaction between Kupffer cells and leukocytes - G. A. Wanner; C. J. Busch; B. Vollmar; M. D. Menger (Inflammation Research, 2004)

A Statistical Approach to Estimate Spatial Distributions of Wet Deposition in Germany - W. Vautz; A. U. Busch; W. Urfer; D. Klockow (Water, Air, & Soil Pollution, 2003)

Genetic Variation and Relationships of Constitutive and Herbivore-Induced Glucosinolates, Trypsin Inhibitors, and Herbivore Resistance in Brassica rapa - Donald F. Cipollini; Jeremiah W. Busch; Kirk A. Stowe; Ellen L. Simms; Joy Bergelson (Journal of Chemical Ecology, 2003)

Dependence of I Ks biophysical properties on the expression system - Seebohm G.; Lerche C.; Busch A.; Bachmann A. (Pflügers Archiv - European Journal of Physiology, 2001)

Interaction between electron transport at the plasma membrane and nitrate uptake by maize (Zea mays L.) roots - D. Steffen; O. Dring; M. A. Busch; M. Bttger; S. Lthje (Protoplasma, 2001)

Degradation of desferrioxamines by Azospirillum irakense: Assignment of metabolites by HPLC/electrospray mass spectrometry - G. Winkelmann; B. Busch; A. Hartmann; G. Kirchhof; R. Süßmuth; G. Jung (BioMetals, 1999)

DNA fingerprinting reveals polygyny in the subterranean rodent Ctenomys talarum - Roxana R. Zenuto; Eileen A. Lacey; Cristina Busch (Molecular Ecology, 1999)
DNA fingerprinting was used to characterize patterns of paternity in two populations of Ctenomys talarum from Buenos Aires Province, Argentina. The multilocus probe PV47–2 was used to detect variation in genomic DNA extracted from 12 females, their 32 offspring, and 14 putative sires. For 11 out of 12 litters examined, a single male capable of providing all nonmaternal bands was identified. Within each study population, individual males sired more than one litter, suggesting that C. talarum is polygynous. No evidence of multiple paternity of litters was found. High band‐sharing values among females suggest that further research is needed to assess the population genetic structure of this species.

Water relations of riparian plants from warm desert regions - Stanley D. Smith; Dale A. Devitt; Anna Sala; James R. Cleverly; David E. Busch (Wetlands, 1998)

Effect of extracellular pH on the myo -inositol transporter SMIT expressed in Xenopus oocytes - J. Matskevitch; C. A. Wagner; T. Risler; H. M. Kwon; J. S. Handler; S. Waldegger; A. E. Busch; F. Lang (Pflügers Archiv - European Journal of Physiology, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Chloride Conductance and P i Transport are Separate Functions Induced by the Expression of NaPi-1 in Xenopus Oocytes - S. Bröer; A. Schuster; C.A. Wagner; A. Bröer; I. Forster; J. Biber; H. Murer; A. Werner; F. Lang; A.E. Busch (The Journal of Membrane Biology, 1998)

Electrophysiological Characterization of the Flounder Type II Na + /P i Cotransporter (NaPi-5) Expressed in Xenopus laevis Oocytes - I.C. Forster; C.A. Wagner; A.E. Busch; F. Lang; J. Biber; N. Hernando; H. Murer; A. Werner (The Journal of Membrane Biology, 1997)

K V LQT channels are inhibited by the K + channel blocker 293B - M. Bleich; M. Briel; A. E. Busch; H. J. Lang; U. Gerlach; H. Gögelein; R. Greger; K. Kunzelmann (Pflügers Archiv - European Journal of Physiology, 1997)

Net proton secretion as a parameter for nitrate uptake - M. A. Busch; M. Bttger (Protoplasma, 1997)

Lack of interaction between meloxicam and warfarin in healthy volunteers - D. Türck; C. A. P. F. Su; G. Heinzel; U. Busch; E. Bluhmki; J. Hoffmann (European Journal of Clinical Pharmacology, 1997)

Control of food influx by temporal subcastes in the fire ant, Solenopsis invicta - A. Ann Sorensen; Tana M. Busch; S. Bradleigh Vinson (Behavioral Ecology and Sociobiology, 1985)

ber die Zusammensetzung von Involutionsformen der Mikroorganismen - A. Rippel-Baldes; G. Busch; F. Radler (Archives of Microbiology, 1956)